Hα Moreton waves observed on December 06, 2006 - Francile, Carlos Natale (2013)
We present high temporal resolution observations of a Moreton wave event detected with the Hα Solar Telescope from Argentina (HASTA) in the Hα line 656.3nm, on December 6th, 2006. Aims. The aim is to contribute to the discussion about the nature and triggering mechanisms of Moreton wave events. Methods. We describe the HASTA telescope capabilities and the observational techniques developed. We carry out a detailed analysis of the radiant point as probable origin of the event. There are different radiant point determinations depending on non?discernible interpretations of the observations. We use a 2D reconstruction of the HASTA and the corresponding TRACE observations, together with conventional techniques, to analyse the coronal nature of the phenomenon. Results. Chromosphere: The kinematic parameters of the Moreton wave event, associated with a X6.5 flare, are determined. Corona: Small-scale ejecta and the winking of remote filaments are analysed to discuss the type of coronal MHD wave that can originate the observed patterns in Hα images and its probable origin. The results strongly depend on the radiant point determination and motion. Conclusions. The detailed analysis of the Moreton wave event favors the hypothesis that the phenomenon can be described as the chromospheric imprint of a single fast coronal shock whose origin could be related to a flare pressure pulse, although a CME origin can not be discarded.